Perspektif Fraud Hexagon Theory dalam Perilaku Academic Fraud: Studi Explanatory pada Mahasiswa Akuntansi - Moorcy, Putri Arini; Sarwani, Sarwani; Suhaili, Achmad; Rasidah, Rasidah (Owner : Riset dan Jurnal Akuntansi, 2024)
Fraudulent behavior has become the center of attention recently. Fraud also occurs in the academic world, better known as academic fraud. The purpose of this research is to examine and analyze the influence of (1) pressure on academic fraud behavior of accounting students in Banjarmasin; (2) opportunity to  academic fraud behavior of accounting students in Banjarmasin; (3) rationalization to academic fraud behavior of accounting students in Banjarmasin; (4) capability to academic fraud behavior of accounting students in Banjarmasin; (5) ego to academic fraud behavior of accounting students in Banjarmasin; and (6) collusion to academic fraud behavior of accounting students in Banjarmasin. The population of this study is 2,404 accounting students in PTN or PTS in Banjarmasin. At the same time, the sample of this study was derived based on Yount’s sampling percentage table. There are 120 students determined as the sample. The data were collected by deploying a google form questionnaire to the respondents. The data was then analyzed using the multiple linear regression method. This study concludes that only rationalization and capability significantly influence the academic fraud behavior of accounting students in Banjarmasin. At the same time, the other elements of fraud hexagon, such as pressure, opportunity, ego, and collusion did not significantly influence the academic fraud behavior of accounting students in Banjarmasin. The results of the research serve as input for academics to improve the learning system and make efforts to minimize opportunities for academic fraud by students. These efforts can be made by improving the control system during exams and self-assessment assignments